Angiogenic potential of extracellular matrix of human amniotic membrane - Md Hashim, Siti Nurnasihah; Hilmi Yusof, Muhammad Fuad; Zahari, Wafa’; Ahmad Amin Noordin, Khairul Bariah; Kannan, Thirumulu Ponnuraj; Sheikh Abdul Hamid, Suzina; Mokhtar@Makhtar, Khairani Idah; Ahmad, Azlina (Kluwer Academic Publishers-Springer, 2016)
Combination between tissue engineering and other fields has brought an innovation in the area of regenerative medicine which ultimate aims are to repair, improve, and produce a good tissue construct. The availability of many types of scaffold, both synthetically and naturally have developed into many outstanding end products that have achieved the general objective in tissue engineering. Interestingly, most of this scaffold emulates extracellular matrix (ECM) characteristics. Therefore, ECM component sparks an interest to be explored and manipulated. The ECM featured in human amniotic membrane (HAM) provides a suitable niche for the cells to adhere, grow, proliferate, migrate and differentiate, and could possibly contribute to the production of angiogenic micro-environment indirectly. Previously, HAM scaffold has been widely used to accelerate wound healing, treat bone related and ocular diseases, and involved in cardiovascular repair. Also, it has been used in the angiogenicity study, but with a different technical approach. In addition, both side of HAM could be used in cellularised and decellularised conditions depending on the objectives of a particular research. Therefore, it is of paramount importance to investigate the behavior of ECM components especially on the stromal side of HAM and further explore the angiogenic potential exhibited by this scaffold.